Answer:
A) y = -5/8x + 6
Step-by-step explanation:
y2 - y`1 / x2 - x1
7/2 - 11 / 4 - (-8)
-15/2 / 12
= -5/8
y = -5/8x + b
11 = -5/8(-8) + b
11 = 5 + b
6 = b
Answer: 945
Step-by-step explanation:
this month = 450.
next month 450x10/100=45, 450+45= 495
450+495= 945
Answer:
125/1000 and no hes not correct
Step-by-step explanation:
Answer: x = (-3,3), y = (-5,5)
Step-by-step explanation:
Add both of the equations together, for
. Now we can divide both sides by 3, getting
. we subtract the first equation from our equation we just got, getting
y= (5,-5). once we plug that in, we get
,
x = (-3,3)